We are the union : democratic unionism and dissent at Boeing - Cloud, Dana L. (University of Illinois Press, 2011)
Shows how ordinary workers attempted to take command of their futures by chipping away at the cosy partnership between union leadership & corporate management. Focusing on the 1995 strike at Boeing, Cloud renders a multi-layered account of the battles between company & the union & within the union led by Unionists for Democratic Change.